Trichoderma Species Differ in Their Volatile Profiles and in Antagonism Toward Ectomycorrhiza Laccaria bicolor - Guo, Yuan; Ghirardo, Andrea; Weber, Baris; Schnitzler, Jörg-Peter; Benz, J. Philipp; Rosenkranz, Maaria (Frontiers in Microbiology, 2019)
Fungi of the genus Trichoderma are economically important due to their growth-promoting effects, such as improved nutrient supply, mycoparasitism of plant-pathogens and priming of the plant defense. Due to their mycotrophic lifestyle however, they might also be antagonistic to other plant-beneficial fungi, such as mycorrhiza-forming species. Trichoderma spp. releases a high diversity of volatile organic compounds (VOCs), which likely play a decisive role in the inter-species communication. It has been shown that Trichoderma VOCs can inhibit growth of some plant pathogens, but their inhibition potentials during early interactions with mutualistic fungi remain unknown. Here, we investigated the VOC profiles of three isolates of Trichoderma species, T. harzianum, T. hamatum and T. velutinum, as well as the common ectomycorrhizal fungus Laccaria bicolor by stir bar sorptive extraction and gas chromatography – mass spectrometry (SBE-GC-MS). We further examined the fungal performance and the VOC emission profiles during confrontation of the Trichoderma species with L. bicolor in different co-cultivation scenarios. The VOC profiles of the three Trichoderma species were highly species-dependent. T. harzianum was the strongest VOC emitter with the most diverse compound pattern, followed by T. hamatum and T. velutinum. Co-cultivation of Trichoderma spp. and L. bicolor altered the VOC emission patterns dramatically in some scenarios. The co-cultivations also revealed contact degree-dependent inhibition of one of the fungal partners. Trichoderma growth was at least partially inhibited when sharing the same headspace with L. bicolor. In direct contact between both mycelia, however, L. bicolor growth was impaired, indicating that Trichoderma and L. bicolor apply different effectors when defending their territory. Multivariate analysis demonstrated that all examined individual fungal species in monoxenic cultures, as well as their co-cultivations were characterized by a distinct VOC emission pattern. The results underline the importance of VOCs in fungal interactions and reveal unexpected adjustability of the VOC emissions according to the specific biotic environments.